Respons Fans Janiwota terhadap Berita Jhonny's Jimusho dalam Media Sosial Twitter - Soemantri, Nadya Alyana; Muchlisian, Asep Achmad; Putri, Yuliani Kusuma (Jurnal SORA - Pernik Studi Bahasa Asing, 2023)
This research examines "Janiwota's Response to Johnny's Jimusho News on Twitter Social Media: Netnographic Study". The aim of this research is to find out the topics uploaded, as well as find out the responses and interactions given by fans to the news uploaded by the official Jhonnys & Associates Twitter account. The method used is a qualitative method with a netnographic approach. Data collection was carried out by accessing the discussion archives of the idol groups Travis Japan and Naniwa Danshi, which were then analyzed by categorizing the data obtained according to theory. The research results show that more news posts about Travis Japan were uploaded in March, and Naniwa Danshi was more uploaded in February. Uploads on various Twitter social media accounts have generated many different responses and reactions from fans from various countries.